Outcomes of Concussion Injuries to Running Backs and Wide Receivers in the National Football League. Issue 7 (29th July 2019) - Okoroha, Kelechi R.; Jildeh, Toufic Raja; Taylor, Kevin; Buckley, Patrick; Mehta, Samir; Moutzouros, Vasilios
Objectives: Concussion injuries are common in professional football players, however the impact on player careers remains unclear. The purpose of this study was to quantify the effect of concussions on professional football player performance. Methods: Concussion data from the National Football League was collected for a period of four seasons (2012-2015) for running backs and wide receivers. Demographic variables (age, experience, position, time to return, yearly total yards and touchdowns) were recorded. Power ratings (total yards divided by 10 plus touchdowns multiplied by 6) were calculated for the injury season as well as for the 3 seasons before and after the injury. A control group consisted of running backs and wide receivers without an identified concussion injury who competed in the 2014 season. Results: One hundred and eighteen running backs and wide receivers sustained a concussion over a 4-season period, 25 players (21%) never returned to a National Football League game. Players were able to return in an average of 18.5 ± 8.2 days, missing 1.6 ± 1.0 games. For 18 players with a minimum total power rating of (sum of 4 seasons) of 200 points, power rating per game decreased 43.4 ± 0.4 points from three seasons prior to the concussion to three years postinjury. This change in performance was not statistically significant (P=0.422) when compared with the change for the 343 control players. Conclusion: Over one fifth of National Football League running backs and wide receivers who sustain a concussion never return to play in a game. On return to competition, player performance of injured players reduced from before injury, however there was no difference compared to controls.